Maqashid Shariah-Based Development Strategy of Village-Owned Enterprise (BUMDes) for Sustainable Economic Empowerment in Jambu Village - Dio Pranata; Chuzaimah Batubara (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the development strategy of the Village-Owned Enterprise (BUMDes) Jambu in Jambu Village using the maqashid shariah approach as an effort to realize sustainable economic empowerment. The research employs a qualitative approach with in-depth interviews, observation, and documentation study techniques. The findings indicate that the development strategy focuses on optimizing local potential through three main business units: the Savings and Loan Unit, printing services, and the agricultural sector. This approach aligns with the concept of Falah, which integrates material and spiritual well-being. However, its implementation still faces several challenges, including limited production facilities, weak institutional management, low community participation, and suboptimal integration of maqashid shariah values. The principle of hifzh al-mal has been applied through business financing access, but Islamic financial literacy remains limited, while the aspects of hifzh al-nafs and hifzh al-‘aql have not yet been strengthened through systematic training and education